Inflammation and Tissue Remodeling in the Bladder and Urethra in Feline Interstitial Cystitis - Kullmann, F. Aura; McDonnell, Bronagh M.; Wolf-Johnston, Amanda S.; Lynn, Andrew M.; Giglio, Daniel; Getchell, Samuel E.; Ruiz, Wily G.; Zabbarova, Irina V.; Ikeda, Youko; Kanai, Anthony J.; Roppolo, James R.; Bastacky, Sheldon I.; et al. (Frontiers in Systems Neuroscience, 2018)
Interstitial cystitis/bladder pain syndrome (IC/BPS) is a debilitating chronic disease of unknown etiology. A naturally occurring disease termed feline interstitial cystitis (FIC) reproduces many features of IC/BPS patients. To gain insights into mechanisms underlying IC/BPS, we investigated pathological changes in the lamina propria (LP) of the bladder and proximal urethra in cats with FIC, using histological and molecular methods. Compared to control cat tissue, we found an increased number of de-granulated mast cells, accumulation of leukocytes, increased COX-1 expression in the bladder LP, and increased COX-2 expression in the urethra LP from cats with FIC. We also found increased suburothelial proliferation, evidenced by mucosal von Brunn’s nests, neovascularization and alterations in elastin content. Scanning electron microscopy revealed normal appearance of the superficial urethral epithelium, including the neuroendocrine cells (termed paraneurons), in FIC urethrae. Together, these histological findings suggest the presence of chronic inflammation of unknown origin leading to tissue remodeling. Since the mucosa functions as part of a ‘sensory network’ and urothelial cells, nerves and other cells in the LP are influenced by the composition of the underlying tissues including the vasculature, the changes observed in the present study may alter the communication of sensory information between different cellular components. This type of mucosal signaling can also extend to the urethra, where recent evidence has revealed that the urethral epithelium is likely to be part of a signaling system involving paraneurons and sensory nerves. Taken together, our data suggest a more prominent role for chronic inflammation and tissue remodeling than previously thought, which may result in alterations in mucosal signaling within the urinary bladder and proximal urethra that may contribute to altered sensations and pain in cats and humans with this syndrome.